2020
DOI: 10.1017/s0305000919000916
|View full text |Cite
|
Sign up to set email alerts
|

Children's epistemic inferences through modal verbs and prosody

Abstract: This study explores how young children infer nuances in epistemic modality through prosody. A forced-choice task was used, testing children's (ages three to seven) comprehension of the might/will distinction (modal condition) as well their ability to modulate the strength of might through two prosodic tunes (prosody condition). Positive and negative valence conditions were included. Younger children were shown to start off performing above chance for the modal condition, and at around chance for the prosody co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Some 4.5-to 6-year-olds distinguish what has to be the case from what may be the case (Öztürk & Papafragou (2015), experiments 1 and 2), and some and 4-to 5.5-year-olds distinguish what is the case from what may be the case (Öztürk & Papafragou (2015), experiment 3). A small proportion of 3-year-olds might distinguish what will happen from what might happen (Armstrong 2020). We have shown that some 4-year-olds distinguish what can happen from what has to happen.…”
Section: Discussionmentioning
confidence: 63%
“…Some 4.5-to 6-year-olds distinguish what has to be the case from what may be the case (Öztürk & Papafragou (2015), experiments 1 and 2), and some and 4-to 5.5-year-olds distinguish what is the case from what may be the case (Öztürk & Papafragou (2015), experiment 3). A small proportion of 3-year-olds might distinguish what will happen from what might happen (Armstrong 2020). We have shown that some 4-year-olds distinguish what can happen from what has to happen.…”
Section: Discussionmentioning
confidence: 63%
“…It is unclear how children behave in this respect. Nevertheless, prosody has been shown to modulate the interpretation of modals in both adults and children, in particular, in identifying epistemic stances such as disbelief (Armstrong 2014(Armstrong , 2020. For instance, when hearing two twins react to a statement in two different ways (with a neutral echo or a disbelief echo), children were able to accurately identify the twin who distrusted the speaker to a great extent, though not fully adult-like.…”
Section: What Is the Role Of Prosody?mentioning
confidence: 99%